The crime of commercial concealment and its impact on the national economy according to the Saudi system - Amira Mohammed Ibrahim Sati (International Journal of Law Research and Studies, 2025)
This research titled "The Crime of Commercial Concealment and Its Impact on the National Economy According to the Saudi System" includes an introduction discussing the research topic, its importance, associated problems, objectives, and methodology. The scope of the study focuses on the crime of commercial concealment within the Saudi system. The research is divided into three sections: the first section is titled "What is the Crime of Commercial Concealment," the second section discusses "The Causes of Commercial Concealment and Its Impact on Society and the National Economy," and the third section is titled "The Role of Government Agencies in Combating Commercial Concealment, Its Penalties, and Methods to Eliminate It." Each section is further divided into subsections, followed by a conclusion that includes findings and recommendations, alongside the search indexes. In the first section, we addressed the nature of commercial concealment and defined the crime and its elements. In the second section, we discussed the causes of commercial concealment and its impact on society and the national economy. In the third section, we examined the role of government agencies in combating commercial concealment, its penalties, and ways to eliminate it. In conclusion, we presented results and recommendations reached through the study, analysis, and discussion of the research topics. Among the most significant findings are:-      Negative impacts on the national economy, as the results revealed that commercial concealment adversely affects the national economy by reducing government revenues from taxes and fees and increasing unfair competition in the markets.-      A lack of legal awareness, as the study showed a significant deficiency in awareness regarding commercial concealment and its associated risks, which facilitates the spread of this phenomenon among individuals and companies.As for the recommendations, the most important include the following:-      The need for international cooperation, as the results indicated the necessity of enhancing collaboration with international and local entities in combating commercial concealment and exchanging information to strengthen ongoing efforts.-      Strengthening institutional oversight, as the results emphasized the importance of enhancing institutional oversight over commercial activities, including the use of technology to track and monitor suspicious commercial activities.
Keywords: Commercial concealment; combating; economic impacts; penalties; crime